Prevalence and associated factors of sexual dysfunction in Malaysian menopausal women - Malini Mat Napes,,; Hatta Sidi,; Shuhaila Ahmad,; Norzilawati Mohd Naim,; Marhani Midin,; Mohd Zulkifli Mohd Kasim,; Rahima Dahlan,; Tan, Lee Khing; Ng, Chong Guan (Universiti Kebangsaan Malaysia, 2013)
The complexity of physical, hormonal and psychocological changes in menopause may affect the sexual function in women. This study measured the prevalence of female sexual dysfunction (FSD) in Malaysian menopausal women. The associated factors were also examined in the study. A cross-sectional study involved 310 menopausal (defined as last menstrual period more than 12 months ago) who visited a menopausal clinic in a secondary referral hospital in the East Peninsular Malaysia. The prevalence and associated factors of female sexual dysfunction in the study subjects were determined. Sexual dysfunction was assessed using the Malay version of the female sexual function index (MVFSFI). Possible associated factors were collected in a pre-designed questionnaire. The prevalence of FSD for the menopausal women was 21.3%. Younger age was the only factor significantly associated with FSD in the study subjects (adjusted odds ratio=0.916, 95% CI=0.851-0.987). The prevalence of FSD was low in the Malaysian menopausal women and associated with younger age.